Analisis Perilaku Biaya Dalam Membuat Keputusan Menerima atau Menolak Pesanan Khusus Pada PT. Putra Sejati - Erawati Kartika (Universitas Muhammadiyah Semarang, 2019)
Economic growth and business in the era of globalization require all companies to obtain maximum profits. To run a business requires information. Information is required by management to reduce uncertainty in decision making. The purpose of this study is to apply cost behavior analysis in making decisions to accept or reject special orders. The method used is descriptive quantitative. The results show that management has not implemented cost behavior analysis in separating fixed costs and variable costs. The results of the cost behavior analysis, especially the decision making to accept or reject special orders, show that the proposed alternatives are able to accept special orders, because the selling price of the special order is greater than the variable cost. Management of PT. Putra Sejati should start implementing cost behavior analysis so that special orders can be used as an alternative to increase company profits.